(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Objective: As an input for the establishment of propagation and conservation protocols, the seed storage potential of Abarco (Cariniana pyriformis Miers) and Mahogany (Swietenia macrophylla King), forest species in a threatened category, was evaluated. Method: This prospective study was carried out in the Biotechnology laboratory of the Center for Studies and Research in Biodiversity and Biotechnology of the University of Quindío (CIBUQ), performing preliminary quality tests, which included biological germination tests in Petri dishes at room temperature (23°C), moisture content with a halogen chamber and viability tests with tetrazolium [1] (ISTA, 2017) at 0.5% and 1% at 40°C for one hour and at room temperature for 24 hours. Subsequently, storage tests were performed at three temperatures (-20°C, 5°C and room temperature 23°C), using airtight glass containers. Quality monitoring was carried out after three and six months of storage. The tests were carried out on samples of 100 seeds per procedure. Results: According to the biological germination test, mahogany and Abarco seeds showed values of 90% and 60%, respectively, with moisture contents of 4.4 and 8% prior to storage. The viability test was standardized at room temperature for 24 hours, in concentrations of tetrazolium at 0.5 and 1% for Mahogany and 0.5% for Abarco with the exposure of the seeds for 1 hour at 40°C. The evaluation of quality after storage indicated that the viability of seeds stored at 5°C and at room temperature was maintained in both species, mahogany with 90% and 55% and Abarco with 87% and 49%, respectively. Moisture content was more stable in mahogany with variations from 0.6 to 0.92% at the three temperatures, while in Abarco it ranged from 1.0 to 1.6% with respect to the initial value. Both species showed a decrease in viability or germination capacity at -20°C three and six months after storage, with values of 20 and 18% for mahogany and 15 and 12% for Abarco. Discussion: The different topographic staining patterns obtained coincide with those reported in the literature, although they differ in the standardization of the viability test. However, the average viability values, 85% for Caoba and 73% for Abarco, are close to some records. On the other hand, and in relation to seed quality parameters under storage conditions, the results ratify the orthodox characteristics of the species. Some authors consider that the heterogeneity of forest seeds does not allow the homologation of the same storage technique, since many show a favorable response to storage, while others, on the contrary, deteriorate rapidly under the same conditions. The literature reports some authors who validated the storage of these forest species with 3-7% humidity at low temperatures, maintaining germination percentages of 80-95%, with progressive loss over time, since the reduction of humidity reduces the possibility of germination by causing alterations in the subcellular structure. Given the orthodox characteristics of the seeds of these species, it is feasible to explore ultra-dry storage at less than 3% moisture content, for several months regardless of storage temperature. Conclusions: To promote the conservation of these forest species and the commitment to sustainable use, it is necessary to count, among other strategies, with the constant provision of seeds. In this sense, it is possible to monitor viability with 0.5 and 1% tetrazolium concentrations for 1 and 24 hours at 40°C and room temperature, and to maintain germination capacity for six months with seed storage at 5°C and low moisture content (4 to 8%).